2013
DOI: 10.1016/j.jaci.2013.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker surrogates do not accurately predict sputum eosinophil and neutrophil percentages in asthmatic subjects

Abstract: Background Sputum eosinophils (Eos) are a strong predictor of airway inflammation, exacerbations, and aid asthma management, whereas sputum neutrophils (Neu) indicate a different severe asthma phenotype, potentially less responsive to TH2-targeted therapy. Variables such as blood Eos, total IgE, fractional exhaled nitric oxide (FeNO) or FEV1% predicted, may predict airway Eos, while age, FEV1%predicted, or blood Neu may predict sputum Neu. Availability and ease of measurement are useful characteristics, but ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
166
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(188 citation statements)
references
References 69 publications
(121 reference statements)
21
166
1
Order By: Relevance
“…The main finding of this study is the increased expression of IL-1R family members in distinguish between the various inflammatory profiles in sputum (24). FeNO levels and blood 428 eosinophil counts were similar and highest in the eosinophilic and mixed group but equally 429 low in the neutrophilic and pauci-granular groups, mirroring the findings of Hastie and 430 colleagues (24).…”
supporting
confidence: 68%
“…The main finding of this study is the increased expression of IL-1R family members in distinguish between the various inflammatory profiles in sputum (24). FeNO levels and blood 428 eosinophil counts were similar and highest in the eosinophilic and mixed group but equally 429 low in the neutrophilic and pauci-granular groups, mirroring the findings of Hastie and 430 colleagues (24).…”
supporting
confidence: 68%
“…Of a range of different biomarkers, blood eosinophil counts offer the greatest diagnostic accuracy for sputum eosinophilia, with increasing specificity as blood eosinophil counts increase 28,29 . However, given the natural variability of blood eosinophil counts (even within 24 hours) and their sensitivity to corticosteroids, low blood eosinophil counts may belie clinically significant eosinophilic airway inflammation 13,30,31 . The results of the current analyses underscore the potential limitations of defining probable responders to eosinophil depletion therapy, based on a blood eosinophil count of !300 cells/lL alone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, eosinophil counts in peripheral blood have become popular in identifying asthma patients with airway eosinophilia, in particular in studies with anti-IL-5 therapies [5]. However, although there exists a significant association between eosinophils in blood and in sputum, the use of blood eosinophils to identify sputum eosinophilia is still debated because of the relatively high false-negative and false-positive rates [26]. This was illustrated in the 328 patients of the severe asthma research programme (SARP) showing that the accuracy of blood eosinophils to predict sputum eosinophilia was low, leading to considerable misclassification of patients with eosinophilic or non-eosinophilic asthma.…”
Section: Blood Eosinophilsmentioning
confidence: 99%
“…Many studies have shown a positive relationship between FeNO and the number of percentage sputum eosinophils [23,32,33], and one study showed that FeNO measurement could identify the subgroup of patients with severe eosinophilic asthma [34]. However, in the SARP study, a high rate of misdiagnosis was found when using FeNO for diagnosing eosinophilic asthma based on sputum eosinophils ≥2% [26]. One possible explanation for this discrepancy might be that FeNO values in severe asthma can be confounded by many factors [30].…”
Section: Fenomentioning
confidence: 99%
See 1 more Smart Citation